Penguatan Kewirausahaan Mahasiswa Integrasi Dengan UMKM Kopi - Angga Sugiarto; Suyanta Suyanta; Sukini Sukini; Wiwin Renny Rahmawati (Journal of Midwifery in Community (JMC), 2024)
Today's students, including those in diploma (D3) and bachelor (S1) nursing programs, are developing an entrepreneurial spirit as online businesses become more popular. The inclusion of entrepreneurship courses has further enhanced their knowledge and skills in this area. A key challenge in entrepreneurship is ensuring the availability of products and effective marketing methods. In this community service project, students were introduced to a coffee MSME (Micro, Small, and Medium Enterprise). They learned about coffee from the stages of harvesting, grinding,drying, roasting, milling, to packaging. This activity was conducted in collaboration with coffee farmers in Temanggung. The products were marketed online and showcased at the Central Java Expo and the Poltekkes (Health Polytechnic) Education Expo across Indonesia. As a result, both the MSMEs and students improved their packaging and marketing skills. Additionally, MSME product sales and student profits increased. It is recommended that similar models be implemented in other regions to foster entrepreneurship more broadly.